PERFORMANCE EVALUATION OF SDN CONTROLLERS: FLOODLIGHT AND OPENDAYLIGHT - Rowshanrad, Shiva; Abdi, Vajihe; Keshtgari, Manijeh (IIUM Engineering Journal, 2016)
Software Defined Network is new network architecture. One of its components is the controller, which is the intelligent part of SDN. Many controllers such as Floodlight, Open Daylight, Maestro, NOX, POX and many others are released. The question is which controller can perform better in which situations. Many works were done to compare controllers regarding architecture, efficiency and controllers’ features. In this paper, two of the most popular controllers, Floodlight and OpenDaylight are compared in terms of Network QoS parameters such as delay and loss in different topologies and network loads. This paper can help researchers to choose the best controller in different use cases such as clouds and multimedia. The results with 95% confidence interval show that OpenDaylight outperforms Floodlight in low loaded networks and also for tree topology in mid loaded networks in terms of latency. Floodlight can outperform OpenDaylight in heavy loaded networks for tree topology in terms of packet loss and in linear topology in terms of latency. There is no significant difference in performance of Floodlight and OpenDaylight controllers in other cases.